Antibiotic Susceptibility Patterns of Pseudomonas spp. Isolated from Soil Samples - Badiyya Hassan Mashi (UMYU Journal of Microbiology Research)
Antimicrobial resistance is one of the major problems facing the health sector. This has to do with many factors including changes in metabolic pathways and transfer of virulence genes among bacterial species among others. Therefore, this study aimed at testing the antibiotic susceptibility patterns of Pseudomonas spp. isolated from soil samples using the mastering-S (M13 and M14 disc). In this study, the susceptibility of 25 pseudomonas isolated from soil environment were tested using the mastering-S (13 and 14 disc). Overnight KB* cultures were used to inoculate KB* plates using the spread plate technique before placing the antibiotic disc on the surface of the agar and incubated at 20oC for 48hours. Antibiotic susceptibility was recorded based on the diameter of zone of inhibition. A diameter of 8mm and above was recorded as positive (susceptible) and a value of less than 8mm as negative (resistance). The results show that, all 25 isolates (100%) tested resistant to at least eight (8) antibiotics, while all the strains were susceptible to 10 µg Gentamicin (GM). Similarly, at least 8% were susceptible to 25 µg Chloramphenicol (C), 96% are susceptible to 10 µg Streptomycin (S) and about 92%, 40% and 48% of the isolates were found to be susceptible to 25 µg Tetracycline (T), 25 µg Colistin Sulphate (CO) and 200 µg Sulphatriad (ST) respectively. Therefore, the study concludes that different species of pseudomonad may respond to antibiotic differently and this should be considered especially when selecting drug of choice in medical settings.